Study on the Law of Storage Fatty Acid Value of Paddy with Storage Temperature and Humidity Accumulation - ZHU Ying-ying; YIN Jun; BIN Yu-lan; LI Rui-min; ZHANG Yu-rong; ZHANG Zhong-jie (Liang you shipin ke-ji)
In this study, the concept of storage temperature and humidity was clarified, and the storage temperature and humidity equations were defined by analogy with the storage temperature and humidity equations, according to which the relationship between storage temperature and humidity and their fatty acid values during the storage period of rice grains was investigated. The paddy with an initial moisture content of 14% was the research object. Under different storage periods, the base storage temperature and storage humidity under different storage temperatures and humidity conditions had been investigated, and the cumulative storage temperature, cumulative storage humidity, and cumulative storage temperature and humidity, as well as their correlations with fatty acid values were calculated. The model between cumulative storage temperature and humidity and fatty acid value was established and validated.The results showed that in the paper, the base storage temperature for fatty acid value of paddy was 15 ℃ and the base storage humidity was 55%. Cumulative storage temperature, cumulative storage humidity and cumulative storage temperature & humidity were significantly correlated with fatty acid values and positively correlated. The model equation was: Y=48.9×exp(−((x−7.566)/8.637)^2) (R2=0.844 1; RMSE=2.063) where: x is cumulative storage temperature and humidity (℃%d); Y is fatty acid value (mg KOH/100 g). The model was validated R2=0.867 8, RMSE=2.152, the model is more accurate and can provide a new research method for the analysis and prediction of fatty acid values in rice storage practice.